(untitled) (Castilla. Estudios de Literatura, 2010)
This paper tries to explain the literary thinking of Hannah Arendt. Arendt was a disciple of Heidegger, Jaspers and Bultmann, and her thinking moves between philosophy and political theory. But she has a hermeneutics and aesthetics in nuce. The hermeneutics elaborates the concept of understanding, and the aesthetics relates poetry with human production. Arendt studies also the Kritik des Urteils as a model for the political philosophy that Kant never wrote. At the last, Arendt wrote some interesting critical essays about writers in dark times.